2002
DOI: 10.1034/j.1600-065x.2002.18811.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple pathways to tumor immunity and concomitant autoimmunity

Abstract: The immune repertoire contains T cells and B cells that can recognize autologous cancer cells. This repertoire is directed against self, and in some cases altered self (mutations). Priming immune responses against self antigens can be difficult. Strategies are presented using altered self to elicit immunity against self in poorly immunogenic tumor models. Mechanisms underlying immunity to self antigens on cancer cells show that the immune system can use diverse strategies for cancer immunity, in both the immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 46 publications
1
60
0
Order By: Relevance
“…Anti-tumor responses often result in Ig production against self antigens expressed in tumor cells [28][29][30]. Thus, our observations of reduced autoantibody titers in p53 -/-lpr mice are consistent with the observation of decreased Ig deposition in tumors of p53 -/-mice (a possible indication of decreased autoantibody deposition in tumors) [16].…”
Section: Discussionsupporting
confidence: 76%
“…Anti-tumor responses often result in Ig production against self antigens expressed in tumor cells [28][29][30]. Thus, our observations of reduced autoantibody titers in p53 -/-lpr mice are consistent with the observation of decreased Ig deposition in tumors of p53 -/-mice (a possible indication of decreased autoantibody deposition in tumors) [16].…”
Section: Discussionsupporting
confidence: 76%
“…There are a number of vaccination models for melanoma rejection, which have demonstrated successful therapeutic activity with concurrent depigmentation (22,33). It has also been demonstrated that the activation of CD4 ϩ T cells is critical during the immunization phase of the immune response, though other cells may be required in the effector phase (35,76). As a direct result of experimental findings and the isolation of Ag-specific cytotoxic CD8 ϩ T cells from melanoma patients, a concerted effort has focused on the development of therapeutics directed at augmenting cytotoxic CD8 ϩ T cell activity (5,8,20,77).…”
Section: Discussionmentioning
confidence: 99%
“…Soluble HEL (Ͼ0.5 ng/ml) was detected in the serum of 1 of 10 TrpHEL1 and 1 of 12 TrpHEL2 mice (data not shown), suggesting that HEL is relatively well sequestered in the skin. Immunization with melanocyte-specific Ags and adjuvant has been shown to induce depigmentation in a number of mouse models (33)(34)(35)(36). However, immunizing adult TrpHEL1 mice with HEL in CFA resulted in only one mouse of eight tested developing depigmentation, and the diffuse pattern of graying was unlike spontaneous vitiligo (data not shown).…”
Section: The Generation Of Mice Expressing a Melanocyte Neoantigenmentioning
confidence: 93%
“…These APC transport internalized TAA to draining lymph nodes where they present TAA peptides for the activation of tumor-specific cytotoxic and helper T cells at levels sufficient to overcome suppressive Treg activity (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). We have developed a novel method for achieving immune-mediated destruction of tumor lesions, recruitment of APC into the lesions, effective intratumoral targeting of TAA to recruited APC, and induction of a protective anti-tumor immune response by exploiting the naturally produced anti-Gal Ab.…”
Section: Intratumoral Injection Of ␣-Gal Glycolipids Induces Xenografmentioning
confidence: 99%